Cooling and Vertical Motions of Crustal Wedges Prior to, During, and After Lateral Extrusion in the Eastern Alps: New Field Kinematic and Fission Track Data from the Mur‐Mürz Fault System. Issue 3 (2nd March 2020) - van Gelder, I. E.; Willingshofer, E.; Andriessen, P. A. M.; Schuster, R.; Sokoutis, D.
Abstract: New structural and thermochronological (zircon and apatite fission track) data from the eastern most Alps highlight distinct deformation phases affecting the Austroalpine unit along a major sinistral strike‐slip fault system, the Mur‐Mürz fault (MMF). The data link deformation to vertical motions prior to, during, and after the main phase of lateral extrusion of the orogen. Zircon fission track ages document rapid (ca. 15 °C/Myr) and diachronous (eastward younging) cooling and rock exhumation during the latest Cretaceous to Paleocene. Subsequent regional Eocene to early Miocene cooling below the closure temperature of the apatite fission track system occurred at slow rates (ca. 2 °C/Myr), suggesting that the region was not subject to major surface uplift and erosion during that period. Fault kinematic analysis along the MMF document pre‐extrusion NNW‐SSE contraction, middle Miocene syn‐extrusion NE‐SW to NNE‐SSW directed shortening, and Late Miocene E‐W contraction. All phases are characterized by strike‐slip fault regimes. Formation of the complex MMF zone triggered the exhumation of small, fault‐bound crustal blocks within the fault zone as documented by middle Miocene apatite fission track ages. Overall, ages are similar on both sides of the fault suggesting that lateral extrusion along the MMF was not associated with significant differential vertical motions. Local Pliocene rock cooling and exhumation was probably related to the buttressing effect of the underthrust Bohemian basement spur. Whereas large‐scale, post‐extrusion surface uplift of the extruding crustal wedges, such as the "Styrian block, " must have been related to long‐wavelength deformation processes affecting the easternmost Alps. Key Points: Fission track and fault kinematic data document horizontal and vertical motions of fault‐bound crustal blocks in the eastern Eastern Alps Diachronous Late Cretaceous to Paleocene fast cooling of Austroalpine units was followed by slow Eocene‐Oligocene cooling The Mur‐Mürz fault did not accommodate significant differential vertical motions during and after the extrusion of the Styrian block